2018
DOI: 10.3390/ijerph15050904
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Hepatitis E Virus in Roma Settlements: A Comparison with the General Population in Slovakia

Abstract: Hepatitis E infection is one of the most frequent causes of acute hepatitis in the world. Currently five human genotypes with different geographical distributions and distinct epidemiologic patterns are identified. In Slovakia, only rare cases of hepatitis E have been reported in past years. Because the most important risk factors associated with HEV infection include consumption of contaminated pork meat and poor hygienic standards, the aim of the study was to evaluate the prevalence of anti-HEV total antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…However, only 0.7 per cent of Roma tested positive for HCV [ 22 ]. A subpopulation of the same sample was tested for hepatitis E virus (HEV), and 21.5 per cent of Roma tested positive vs. 7.2 per cent of non-Roma [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only 0.7 per cent of Roma tested positive for HCV [ 22 ]. A subpopulation of the same sample was tested for hepatitis E virus (HEV), and 21.5 per cent of Roma tested positive vs. 7.2 per cent of non-Roma [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Notwithstanding the instances mentioned above, Roma have a higher occurrence of communicable diseases than non-Roma. The most common reasons hypothesised by authors for the higher rates of disease are lack of water, poor sanitation and hygiene, crowded living spaces, high-risk sexual behaviours, and exposure to animals and waste [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our intention was to compare illnesses and the process of dying among Roma as described by Augustini in 1775–1776 and as they occur presently. Current studies are mostly oriented towards the characterization of Roma health, behavior and determinants and their comparison with non-Roma [13,14,15,16,17,18,19,20,21,22,23,24,25,26]. The comparison of the states of these topics over time is missing.…”
Section: Discussionmentioning
confidence: 99%
“…Distinct health beliefs and practices among Roma related to illnesses and death have attracted attention from various fields of research [1,2,3,4,5,6,7,8,9,10,11,12]. The current research interest mostly focuses on topics such as the description of Roma health [13], Roma health behaviour [14,15], understanding Roma health [16] and its determinants [17] from the management of most common illnesses among the Roma population [18] and health-mediation programs [19] to comparisons with the non-Roma population regarding specific chronic illnesses [20,21,22,23,24,25,26]. Seemingly, some beliefs and practices are more stable than others, and some are more prone to change over time.…”
Section: Introductionmentioning
confidence: 99%
“…for approximately 40% of 450,000 Slovak Roma (Musinka et al 2014) (see also Figure 1.3), clinical studies have shown greater burdens of various communicable and non-communicable diseases across the life-course (e.g. Antolová et al 2018;Antolová et al 2016;de Courten et al 2003;Drazilova et al 2018;Halánová et al 2018;Hasajova et al 2014;Kristian et al 2013;Rosenberger et al 2014;Rudohradska et al 2012;Sudzinova et al 2015;Sudzinova et al 2013;Veseliny et al 2014). Slovak Roma have also been found to rate their health as worse compared to their non-Roma counterparts, including Introduction Andrej Belak Chapter 1 with a gradient according to levels of segregation (e.g.…”
Section: Roma Vs Non-romoa Health Inequalities In Slovakiamentioning
confidence: 99%